Legal Migration in the United States: Attitudes of Latin-American Migrants in the Context of Inmigration Policies and Repatriations of Mexicans During the Period 1995-2017 - Vega Quesada, Orlando (2018)
This paper make a profile of the attitudes of migrants of Latin-American origin regarding the positive effects of legal migration through a logistic regression model based on data from the survey applied in 2013 by the PEW Research Center to the Hispanic and Latino community. The profile is built within the framework of the integration developed by the United States and Mexico, not only from the economic link, also includes migratory policies and repatriation processes for Mexicans. These interactions lead us to understand that it is a phenomenon of high complexity, which responds to characteristics that change over time and put bilateral relations in constant challenge.